PERBEDAAN PENGAPLIKASIAN EYEBROW COMPACT POWDER DENGAN EYEBROW GEL PADA RIAS PENGANTIN BARAT - Mela Klistiani; Merita Yanita (Jurnal Tata Rias dan Kecantikan, 2021)
The purpose of this study is to a) Knowing the different results of applying eyebrow compact powder to western bridal makeup b) Knowing the different results of applying eyebrow gel to western bridal makeup c) Knowing the differences in the results of applying eyebrow compact powder to eyebrow gel to western bridal makeup. The type of this research is pre-experimental. the sample in this study amounted to 6 people. The data collection technique is purposive sampling. Descriptive data analysis technique by displaying the mean, standard deviation, minimum and maximum values. Analysis of the data used is the independent-sample t-test. The results of the application of cosmetic eyebrow compact powder on western bridal makeup, it was found that the highest value was obtained in the smoothness and preference section, namely 3.57 having very fine criteria and very liking. In the results of the application of eyebrow gel cosmetics on western bridal makeup, it was found that the greatest value was obtained in the accuracy aspect, namely 3.04 having the right criteria. There are differences in the results of the application of eyebrow compact powder and eyebrow gel cosmetics on western bridal makeup on the aspect of accuracy (p=0,377), on the aspect of smoothness (p=0,013), on the aspect of neatness (p=0,015) and the aspect of liking (p=0,002). Based on the results of the research analysis, it was found that there were differences in the analysis of the results of the application of eyebrow compact powder with eyebrow gel in western bridal makeup.